2008
DOI: 10.2478/s11756-008-0027-x
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine regulation of the reproduction in crustaceans: Identification of potential targets for toxicants and environmental contaminants

Abstract: Progress in ecotoxicological research documents that crustaceans are highly vulnerable to diverse chemicals and toxicants in the environment. In particular, pollutants affecting endocrine homeostasis in crustaceans (i.e., endocrine disruptors) are intensively studied, and serious reproductive disorders have been documented. In this review, current knowledge about the endocrine regulation of the crustacean reproduction is put together with the published ecotoxicological data with an attempt to summarize the pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 107 publications
(144 reference statements)
0
23
0
Order By: Relevance
“…Environmental variables such as salinity, temperature and seasonality play vital roles in regulating crustacean physiology, including reproduction, behavior, molting, morphogenesis and feeding (Charmantier-Daures et al, 1994;Fingerman, 1997a;Mazurová et al, 2008;Spanings-Pierrot et al, 2000). We observed that when red phase crabs were transferred into diluted seawater, the percentage of MF increased to nearly 100% at 11°C and 18°C (Nagaraju and Borst, 2008).…”
Section: Effects Of Environmental Factors On Hormone Levels and Repromentioning
confidence: 77%
See 2 more Smart Citations
“…Environmental variables such as salinity, temperature and seasonality play vital roles in regulating crustacean physiology, including reproduction, behavior, molting, morphogenesis and feeding (Charmantier-Daures et al, 1994;Fingerman, 1997a;Mazurová et al, 2008;Spanings-Pierrot et al, 2000). We observed that when red phase crabs were transferred into diluted seawater, the percentage of MF increased to nearly 100% at 11°C and 18°C (Nagaraju and Borst, 2008).…”
Section: Effects Of Environmental Factors On Hormone Levels and Repromentioning
confidence: 77%
“…Alternative techniques have been attempted to stimulate ovarian development, such as administration of gonad inhibitory hormone (GIH) antibody, hormonal level changes by environmental factors such as temperature, salinity and photoperiod, precise functionality of neurotransmitters and double-stranded RNA interference (dsRNAi) to reduce gonad inhibitory peptide transcript. The results from these experiments have revealed the potential (Chang et al, 2001;FanjulMoles, 2006;Mazurová et al, 2008;Nagaraju, 2007;Nagaraju and Borst, 2008;Treerattrakool et al, 2008) to stimulate gonad maturity. So, in this context, I will discuss up-to-date research on gonad regulatory factors and their role in reproductive development.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Chem. 30,2011removal or effects from transplantation or from the addition of organ homogenates (for reviews, see [81][82][83]). Information concerning these neuropeptides has been accumulating from many species, although the number of these neuropeptides in a single species is still uncertain [76].…”
Section: Reproductive Biology Of Amphipodsmentioning
confidence: 99%
“…Indeed, in crustaceans, serotonin is identified as a neurotransmitter that stimulates release of some neurohormones such as crustacean hyperglycemic hormone (CHH) or MIH (Keller and Beyer 1968;Mattson and Spaziani 1985) and inhibits the release of GIH (Kulkarni and Glade 1991;Tinikul et al 2008). Processes regulated by serotonin may become a target for environmentally relevant endocrine disruptors, such as insecticides because of their neurotoxic properties (Brooks et al 2003;Henry et al 2004;Mazurová et al 2008). The assumption on the serotonin involvement in the Vg and VgR gene expressions is supported by the fact that Ruttanakorn et al (2014) observed an increase of the Vg concentration in M. rosenbergii, after serotonin injection.…”
Section: Expression Of Vitellogenin Receptor Genementioning
confidence: 99%